(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This conceptual paper explores the evolution of sustainable marketing, reflecting the increasing importance of environmental and social considerations in business practices. Tracing the development from early ecological marketing in the 1970s to contemporary sustainable marketing strategies, the paper highlights key trends and shifts in focus within the field. The study examines the historical foundations of sustainability marketing, emphasizing the contributions of social and societal marketing, green marketing, and the emergence of sustainable marketing as a strategic business approach. By integrating economic, social, and environmental dimensions, sustainable marketing seeks to balance profitability with societal and planetary well-being. The paper also addresses the challenges and opportunities of implementing sustainable marketing in India, noting the role of consumer awareness, government initiatives, technological advancements, and corporate social responsibility. This comprehensive overview aims to provide valuable insights for academics, practitioners, and policymakers interested in advancing sustainable business practices and promoting responsible consumption.